2021
DOI: 10.1038/s41419-020-03362-4
|View full text |Cite
|
Sign up to set email alerts
|

Legumain promotes tubular ferroptosis by facilitating chaperone-mediated autophagy of GPX4 in AKI

Abstract: Legumain is required for maintenance of normal kidney homeostasis. However, its role in acute kidney injury (AKI) is still unclear. Here, we induced AKI by bilateral ischemia-reperfusion injury (IRI) of renal arteries or folic acid in lgmnWT and lgmnKO mice. We assessed serum creatinine, blood urea nitrogen, histological indexes of tubular injury, and expression of KIM-1 and NGAL. Inflammatory infiltration was evaluated by immunohistological staining of CD3 and F4/80, and expression of TNF-α, CCL-2, IL-33, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 40 publications
3
108
0
Order By: Relevance
“…An inhibitor of HSP90, 2-amino-5-chloro-N,3-dimethylbenzamide (CDDO), blocks necroptosis by inhibiting RIP1 activation, which means HSP90 accelerates RIP1 phosphorylation. Furthermore, consistent with the interaction of HSP90 and GPX4 [ 15 , 16 ], CDDO suppresses GPX4 degradation and ferroptosis formation by blocking chaperone-mediated autophagy [ 164 ]. Another HSP90 inhibitor tanespimycin (17-allylamino-17-demethoxygeldanamycin) has been proved to exert inhibitory effect on both necroptosis and ferroptosis in HT-22 cells treated with TNF- α /zVAD.fmk or erastin [ 164 ].…”
Section: Crosstalk Between Ferroptosis and Necroptosismentioning
confidence: 79%
See 1 more Smart Citation
“…An inhibitor of HSP90, 2-amino-5-chloro-N,3-dimethylbenzamide (CDDO), blocks necroptosis by inhibiting RIP1 activation, which means HSP90 accelerates RIP1 phosphorylation. Furthermore, consistent with the interaction of HSP90 and GPX4 [ 15 , 16 ], CDDO suppresses GPX4 degradation and ferroptosis formation by blocking chaperone-mediated autophagy [ 164 ]. Another HSP90 inhibitor tanespimycin (17-allylamino-17-demethoxygeldanamycin) has been proved to exert inhibitory effect on both necroptosis and ferroptosis in HT-22 cells treated with TNF- α /zVAD.fmk or erastin [ 164 ].…”
Section: Crosstalk Between Ferroptosis and Necroptosismentioning
confidence: 79%
“…Ferroptosis differs from necroptosis in morphological characteristics; developmental steps; and key regulators, inducers, and inhibitors ( Table 1 ). However, increasing evidence has suggested that significant crosstalk occurs between ferroptosis and necroptosis following ischemic stroke [ 15 21 ]. In this review, we summarize the mechanism underlying the crosstalk between necroptosis and ferroptosis in ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, the mevalonate (MVA) pathway subserves the selenocysteine tRNA in order to participate in the synthesis of GPX4, and isopentenyl pyrophosphate (IPP) and COQ10 are the main products of this process (Warner et al, 2000). Notably, the heat shock protein family also affects GPX4; specifically, HSPA5 attenuates erastin-induced GPX4 evanishment while the chaperone-mediated autophagy on the strength of HSP90 antagonizes that matter, possibly hastened by legumain (Zhu et al, 2017;Wu Z. et al, 2019;Chen et al, 2021). Intriguingly, as the micronutrient, selenium (Se) and selenoprotein are integral in several metabolic and endocrine diseases, such as thyroid disease and diabetes, and raising their level has been relevant to insulin-induced, hydrogen peroxide (H2O2)-dependent signaling impairment, resulting in insulin resistance and hyperglycemia (Wang et al, 2016;Kim et al, 2019;Schomburg, 2020).…”
Section: System Xc-gsh-gpx4 Axismentioning
confidence: 99%
“…[31,34b] The heat shock response is an important system for maintaining cellular homeostasis when cells are under stress, such as in the oxidative stress environment during ferroptosis. [51] Therefore, HSPs are also involvement in mediating ferroptosis resistance, however, the broader interconnectivity of HSPs in ferroptosis requires further elucidation.…”
Section: Cma and Ferroptosismentioning
confidence: 99%